Le présent historique et ses fonctions textuelles - Jørgensen, Kathrine Sørensen Ravn (HERMES - Journal of Language and Communication in Business, 1999)
According to some grammarians the use of the historical present tense is a technique for enhancing the dramatic effect of a story by making addressees feel as if they were present at the time of the experience, witnessing events as they occurred. Others have suggested that the historical present represents events as if they were occurring before the speaker’s eyes. My own position on the matter, though, is that the necessity to postulate a “metaphorical shift”, an “as if”, is due to the interpretation of the basic meaning of the present as being contemporality with the speaker’s present and the identification of a speaker (narrator) with an “intradiegetic” participant in the story (character). In support of this position the paper argues that the temporal referential of the present tense is the speech referential, organised by and around the speaker/character. The speech process is an incomplete process with a validation interval closed to the left and open to the right. This property motivates use of the present as a gram-matical vehicle for re-presentation.